As conjunções em cartas de leitor: tecendo a teia do discurso - Santos, David da Silva Riotinto dos (2024)
In pedagogical practice, we observe students being very insecure when they are asked to produce a text. One of the tactics that is no less important than others, but not assimilated in the context of writing, is the property of cohesion, one of the factors that guarantees the textuality and coherence of the text. The lack of mastery of cohesion mechanisms brings problems to the integration of the parts of the text, generating the need to change attitudes in relation to the processes that involve writing as well as teaching the Portuguese language. Given this fact, we seek to understand how students use adversative, concessive and explanatory conjunctions as mechanisms of cohesion in the written production of the reader's letter genre, also observing coherence in the argumentative process. To do so, we start from works related to the text by Koch (1997), Bentes (2006), Cavalcante (2013) and Marcuschi (1983); To make work on gender viable, focusing on this perspective of language teaching, we took Bakhtin's theory (2003) as a basis; regarding cohesion as a set of sequencing strategies that constitute the text, the references were Antunes (2005) and Koch (2021); considerations about text production were based on Serafini (1992), Ferrarezi Júnior and Carvalho (2015); regarding linguistic analysis in text production, we are based on Reinaldo and Bezerra (2013); To facilitate work on the reader's letter genre and the development of students' writing, we based ourselves on Diaz (2016), Mendonça (2008, 2016), Alves Filho (2011). The methodology favored a qualitative approach of an interventionist nature, through participatory research anchored in Esteban (2010) and Paiva (2019). As data generation instruments, we used a didactic sequence, based on Schneuwly and Dolz (2004), associated with participant observation, and data processing based on Bardin (2011). Finally, we created a pedagogical notebook, as a product of the research, with the aim of offering Portuguese language teachers in elementary school a proposal for teaching conjunctions in order to guarantee students the appropriation of writing skills that involve the use of cohesion in reader letters. After the intervention carried out by this research, we noticed changes in the writing of reader letters from students who started to use conjunctions, taking into account their semantic-discursive relationships.